Analisis DNA Mikrosatelit untuk Identifikasi Paternitas pada Beruk (Macaca nemestrina) di Penangkaran Pusat Studi Satwa Primata IPB - Novita Anggraeni; Ellis Dwi Ayuningsih; Dyah Perwitasari Farajallah; Joko Pamungkas (Pusat Studi Satwa Primata LPPM-IPB, 2009)
The increase of population number of pigtailed macaque in Bogor Agricultural University captive breeding facility, was the reason to conduct the research of paternity using microsatellite DNA analysis. Paternity data will be used for determination of Macaca nemestrina colony management. Based on the paternity analysis results showed that in the Koral A, male (No. 6742) is a breeder for offspring (100%), these male is sub-ordinate in that group. Meanwhile, in the Koral B, male (No. 6180) is a breeder for the siblings in that group (92%) this is dominant male, and another male (No. 6747) is 8% of breeder for the existing siblings. On the other hands, the heterozigosity analysis showed that there were ten allele had been detected in locus D1S548, seven alleles in locus D5S820, and six alleles in locus D2S1777 and D3S1768. The amplicon of locus D1SS548, D3S1768, D5S820, D12S1777 are 180-232 bp, 150-178, 189-217, 153-174, respectivelly. The heterozygosis per locus (h) was 0,5168 for D3S1768, D12S1777 and 0,5934 for D1S548. And the average Heterozigosis per all loci detected was 0.5399.Key words: microsatellite DNA, paternity, beruk, Macaca nemestrina